Offshore Site Investigation Geotechnics 8th International Conference Proceedings
DOI: 10.3723/osig17.142
|View full text |Cite
|
Sign up to set email alerts
|

PISA: New Design Methods for Offshore Wind Turbine Monopiles

Abstract: Improved design of laterally loaded monopiles is central to the development of current and future generation offshore wind farms. Previously established design methods have demonstrable shortcomings requiring new ideas and approaches to be developed, specific for the offshore wind turbine sector. The Pile Soil Analysis (PISA) Project, established in 2013, addresses this problem through a range of theoretical studies, numerical analysis and medium scale field testing. The project completed in 2016; this paper s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 16 publications
(24 reference statements)
1
65
0
Order By: Relevance
“…Monopiles are usually located in water of relatively shallow water depth, ranging between 20 to 40 m. It is unclear as to what is the water depth at which monopile foundations become uneconomic. Monitoring of installed structures indicates that actual foundations offer greater stiffness than predicted by existing design methods [18]; more accurate design methods are needed to reduce the weight and required embedment of monopile foundations [19]. For seabed with clay, sand, or chalk stratigraphy, monopiles can be installed using impact hammers or vibratory driving.…”
Section: Monopile Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monopiles are usually located in water of relatively shallow water depth, ranging between 20 to 40 m. It is unclear as to what is the water depth at which monopile foundations become uneconomic. Monitoring of installed structures indicates that actual foundations offer greater stiffness than predicted by existing design methods [18]; more accurate design methods are needed to reduce the weight and required embedment of monopile foundations [19]. For seabed with clay, sand, or chalk stratigraphy, monopiles can be installed using impact hammers or vibratory driving.…”
Section: Monopile Foundationsmentioning
confidence: 99%
“…It was found that the MMC model provided better simulations of the load-displacement response than the MC model when comparing the numerical predictions with physical model test data. The PISA project [19] has presented a new framework for predicting the monotonic lateral behaviour of a monopile foundation, by using the state-of-the-art 3D FE modelling, validated through a medium scale field testing campaign, to calibrate the soil reactions for a simplified and quick to run 1D FE model. Having gained an understanding of the importance of cyclic loading on the monopile lateral capacity and deflection, researchers investigated the effects of short-term and long-term cyclic lateral loadings.…”
Section: Lateral Stabilitymentioning
confidence: 99%
“…Offshore wind energy is a major component of the energy mix for the UK, with 2000 offshore turbines either operational or being constructed, and many more to be constructed over the next few decades [1]. There are ambitious plans for Europe, USA and East Asia.…”
Section: Background To Pisa Projectmentioning
confidence: 99%
“…The PISA (Pile Soil Analysis) Project, run as a £3.5 m joint industry research project, has produced new practical geotechnical design methods that significantly reduce the dimensions and costs for laterally loaded offshore wind turbine monopile foundations [1][2][3]. The work proposes revisions to conservative design approaches that date back 50 years, such as the American Petroleum Institute (API) p-y method [4] typically adopted for monopile design in the UK, with new and innovative ideas.…”
Section: Background To Pisa Projectmentioning
confidence: 99%
“…Cyclically-loaded foundations may suffer from permanent displacements/rotations depending on the cyclic soil response turning into either 'ratcheting' (gradual/steady plastic strain accumulation) or 'shakedown' (no net strain accumulation over a full cycle) . Presently, this issue is attracting special attention in relation to monopiles for offshore wind turbines, that must be designed to ensure proper operational performance under up to 10 8 -10 9 loading cycles (LeBlanc et al, 2010;DNV, 2016;Byrne et al, 2017) -'highcyclic' loading.…”
Section: Introductionmentioning
confidence: 99%